Consumo de medios de comunicación en estudiantes universitarios de la modalidad presencial de la Universidad Técnica Particular de Loja - año 2014. - Guamán Guadalima, Nelly Gabriela (2014)
The presence of the Internet in the media has caused them converge to the digital platform, changing the way of doing journalism and diffusion of information; which has allowed them to be heard, read and watched by digital natives who seek detailed information about important issues of society. In this research, we have known the preferences of consumption among young people, has contributed not only to the easy access to the media that currently consumed the digital natives and in the same way but also helps the Technical University of Loja will succeed in identifying the most appropriate ways of communication and also to use the tools that technology introduces for teaching and learning by applying the media and communication devices. In this context it was determined the most commonly used media (Internet and TV) as well as the tools that the web gives us, Social Networks; which are seen as most suitable means of communication to keep constant communication.